Group-based exercise training in mobility impaired older women : effects of an outpatient multi-component training program on physical performance, mood, functional abilities and social welfare and healthcare costs after acute hospitalization - Timonen, Leena (Kuopion yliopiston julkaisuja, ISSN 1235-0303, 2007)
Abstract.
Keywords: Activities of Daily Living; Frail Elderly; Female; Exercise; Aged, 80 and over; Affect; Muscle Strength; Accidental Falls : economics; Health Care Costs; Gait; Musculoskeletal Equilibrium; ikääntyneet; kuntoutus; kuntoliikunta; vertaisryhmät; sairaalahoito; terveyspalvelut; sosiaalipalvelut; kustannukset; toimintakyky; mieliala; fyysinen kunto; ryhmät; kuntosalit; harjoittelu; liikunta; avohoito; naiset; grupper av likställda; sjukhusvård; hälsovårdstjänster; social service; kostnader; funktionsförmåga; sinnesstämning; fysisk kondition; grupper; motionssalar; träning; motion; äldre; rehabilitering; konditionsträning; öppenvård (hälso- och sjukvård); kvinnor